A new species of Stenopsyche, with descriptions of larvae and females of some species associated by gene sequences (Insecta: Trichoptera) - Xu, Ji-Hua; Sun, Chang-Hai; Wang, Bei-Xin (Zootaxa, 2015)
Twenty-seven individuals of Stenopsyche from An-hui, Shan-xi and Si-chuan provinces, China, were examined and their DNA (mtCOI) sequences were extracted and analyzed. The larva, male, and female of a new species, S. huangshanensis sp. nov., associated by mtCOI gene sequences, are described and illustrated. Larvae and adult females of 3 known species, S. angustata Martynov 1930, S. navasi Ulmer 1926, and S. tienmushanensis Hwang 1957, were successfully associated with their identifiable males; the larvae and females of S. navasi and S. tienmushanensis were described and illustrated for the first time, and the larva and female of S. angustata were re-described and re-illustrated. DNA from identifiable males of Stenopsyche lotus Weaver 1987 was also sequenced, but the larva and female of this species remain unknown. An unknown larva, not associated with an identifiable adult, was described and illustrated as Stenopsyche sp. 1. All the sequences were uploaded to GenBank. All specimens are deposited in the Insect Collection of Nanjing Agricultural University.